Latvijas Republikas Satversmes pieņemšana un tās juridisko institūtu tapšanas vēsturiskais apskats - Jūgs, Juris (Latvijas Universitāte, 2007)
Pirmā Latvijas neatkarības prasība bija 1917. gada 20. novembra "Deklarācija ārvalstīm un tautām", kurā noteica, Latvijas stāvokli - attiecības uz ārieni un iekšējo iekārtu noteiks Satversmes Sapulce un tautas plebiscīts. 1918. gada 17. novembrī Tautas Padome pieņēma Tautas Padomes politisko platformu, ko var uzskatīt par pirmo Latvijas pagaidu konstitūciju. 1918. gada 18. novembrī Tautas Padome proklamē Latvijas valsti. 1920. gadā tika ievēlēta Satversmes Sapulce. 1920. gadā Satversmes Sapulce pieņem Deklarāciju par Latvijas valsti un Latvijas valsts iekārtas pagaidu noteikumus, kuri kopā uzskatāmi par Latvijas otro pagaidu konstitūciju. No 1920. gada līdz 1922. gadam notiek LR Satversmes izstrādāšana. 1922. gada 15. februārī Satversmes Sapulce pieņēma LR Satversmi.

The first claim of Latvians for the formation of an inpendent state was demanded in 1917. 19. November when the Latvian Temporary National Council (the first unofficial parlament of Latvia) adopted the resolution regarding the need to convene the Satversmes assambley. However, only after a year Peoples’s Council (the second unofficial parlament of Latvia) founded State of Latvia in 1918. 18. november. Peoples Council established Peoples Council Political Platform, which is the first unofficial constitution of Latvia (in 1919. 18. november). In 1920 Satversmes Sapulce (Constitutional Assambley of Latvia) was elected. In 1920 Constitutional Assambley of Latvia established Declaration of Latvian Country and Latvian Country Temporary State Sistem, which both are the second unofficial constitution of Latvia. In-between 1920 and 1922 Constitutional Assambley of Latvia developed and discussed Constitution of Latvia. Finally in 1922. 15. february Satversme (Constitution of Latvia) was established.
The establishment of the constitution of the Republic of Latvia and a historical review of its legal institutions creation
Keywords: Juridiskā zinātne